Innovative tensile strength comparison of spherical and disc specimens - Weige Han; Zhengguo Zhu; Hao Zhou; Longzhou Che; Haorui Peng (Scientific Reports)
Abstract Accuracy of tensile strength is crucial for guiding the stable construction of rock engineering. In this study, a spherical specimen was used for testing tensile strength, and its results were compared with Brazilian split method. A numerical analysis of tensile strength was performed for two kinds of specimens using cohesive zone model. The fracture process and acoustic emission (AE) distribution characteristics of spherical and Brazilian disc specimens were analysed to determine similarities and differences between them. During the axial compression, the stress distribution in Brazilian disc specimen was relatively concentrated, which indirectly limited the range of potential fracture surface. The tensile AE events were concentrated in the middle of the specimen. Therefore, the obtained tensile strength tends to be the strength parameter of a certain section. However, the stress concentration zone in a spherical specimen was more widely distributed, showing three-dimensional characteristics, which did not pre-define the potential fracture surface and increased the randomness of rock rupture. Low energy AE events were distributed discretely in three-dimensional space, and high energy AE events constituted a significant fracture surface, which was the weakest rupture surface of the spherical specimen. The results of the spherical specimen had a smaller standard deviation and larger tensile-shear ratio, and the tensile strength obtained is lower than that of the Brazilian disc specimen. Therefore, the tensile strength obtained by a spherical specimen can better reflect the tensile fracture characteristics under three-dimensional state. The result of this study provides a new idea for the tensile strength testing method.